2021
DOI: 10.2147/cmar.s305321
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Use and the Outcome of Metastatic Renal Cell Carcinoma Treated with Sunitinib or Pazopanib

Abstract: Background The anticancer properties of metformin have been suggested in numerous experimental studies and several retrospective clinical studies show that its use is associated with improved outcome of patients with cancer. However, limited data are available for patients with metastatic renal cell carcinoma (mRCC) treated with targeted therapy. The aim of this retrospective study was to assess the impact of the metformin use on survival of mRCC patients treated with sunitinib or pazopanib. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Moreover, studies have shown that metformin has favourable effects on overall survival rates with sunitinib. 43,56 Another multi-TKI sorafenib has been shown to activate AMPK, 57 emphasizing that activation of AMPK may not be the only cause of the metformin-induced right-shift and increase in EC 50 values of the sunitinib dose-response curve as observed in our study. The cause may lie with metformin's downstream targets because metformin has been shown to suppress cisplatininduced apoptotic cell death through an AMPK-independent manner, possibly by upregulation of the Akt survival pathway.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, studies have shown that metformin has favourable effects on overall survival rates with sunitinib. 43,56 Another multi-TKI sorafenib has been shown to activate AMPK, 57 emphasizing that activation of AMPK may not be the only cause of the metformin-induced right-shift and increase in EC 50 values of the sunitinib dose-response curve as observed in our study. The cause may lie with metformin's downstream targets because metformin has been shown to suppress cisplatininduced apoptotic cell death through an AMPK-independent manner, possibly by upregulation of the Akt survival pathway.…”
Section: Discussionsupporting
confidence: 63%
“…As for vorinostat, metformin and vorinostat have shown a synergy in overcoming EGFR tyrosine kinase inhibitor resistance in non-small cell lung cancer (Chen et al, 2017). And finally, as for pazopanib, in a clinical study, the use of metformin was associated with favorable outcome of metastatic renal cell carcinoma patients treated with pazopanib (Fiala et al, 2021). In addition to ATLANTiC associations, the HDAC inhibitor vorinostat was enriched in P-site annotations using the PTMsigDB (Krug et al ., 2019), whereas both vorinostat and paclitaxel emerged when correlating the individual cell line-specific metformin signatures to the drug profiles using the P100 (Abelin et al ., 2016; Dele-Oni et al ., 2021; Litichevskiy et al ., 2018) and PhosFate Profiler (Ochoa et al, 2016) ( Supplementary Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to retrospective research involving patients with metastatic renal cell carcinoma (mRCC), the use of MET in conjunction with the tyrosine kinase inhibitor (TKI) sunitinib was linked to improved overall survival (OS) in patients with diabetes mellitus, compared to the use of other diabetic agents [149]. In another retrospective research, it was investigated that the addition of metformin to sunitinib or an alternative TKI, pazopanib, in patients with mRCC led to better PFS and OS outcomes, irrespective of diabetic status [150].…”
Section: Met As An Anticancer Agent In Clinical Trialsmentioning
confidence: 99%